Positive Aesthetic Assessment of a Product Design Based on the Approach Neotonic Design - Wahyuni, Ruslinda Dwi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Positive assessments from consumers on the products offered are a significant element for creative industry players. Several studies have shown that the main factor determining the decision to buy a product is not the function but the aesthetic appearance of the product. One method of assessing the aesthetics of product design is neotonic design.research was Neotonic design conducted to show how product design characteristics can objectively display a positive aesthetic. This study aims to provide input to creative industry players how consumers give a positive assessment of the outer appearance/aesthetics of product design. To achieve this goal, the research explores the question of how can neotonic design be an important factor in a positive assessment of the aesthetics of a product design? Based on these research questions, two hypotheses were made H1: The cuteness shown will be more visible if the object is smaller than the larger object (H1a), rounder than pointed (H1b), simpler than complex (H1c), brighter than darker (H1d), and wider than taller (H1e). H2: The cuteness that is displayed is related to the positive assessment of aesthetics as an attractive element in the design. The study involved 50 respondents with 34 product design research objects and 28 geometric shapes. The results showed that the complicated dimension was considered funnier than simple. So that the small, round, wide, bright, and complex dimensions become the main markers of consumers' positive (funny) assessment of product design. The five dimensions above show that funny/neotonic designs are an important factor in positive evaluation of the aesthetics of a product design.